A Novel Signature for Predicting Prognosis of Smoking-Related Squamous Cell Carcinoma - Chen, Chang; Cheng, Xiaoqing; Li, Shuyan; Chen, Huanghui; Cui, Mengjing; Bian, Linlin; Jin, Hui (Frontiers in Genetics, 2021)
Tobacco smoking is an established risk factor for squamous cell carcinoma (SCC). We obtained smoking-related SCC, including cervical squamous cell carcinoma (CSCC), esophageal squamous cell carcinoma (ESCC), head and neck squamous cell carcinoma (HNSC), and lung squamous cell carcinoma (LUSC), from the Cancer Genome Atlas (TCGA) database to investigate the association between smoking status (reformed and current smoking) and prognosis. We found reformed smokers had better prognosis than current smokers in CSCC (p=0.003), HNSC (p=0.019) and LUSC (p<0.01) cohorts. Then, we selected LUSC cohorts as the training cohort and other SCC cohorts as the test cohorts. Function analysis revealed that homologous recombination (HR) was the most significant pathway involving in smoking-induced LUSC. Moreover, the effect of cross-talk between the smoking status and homologous recombination deficiency (HRD) on the prognosis were further evaluated, revealing that quitting smoking with high HRD scores could significantly improve patients’ prognosis (p<0.01). To improve prognosis prediction and more effective screen suitable population for platinum drugs and poly-ADP-ribose polymerase (PARP) inhibitors, we constructed the risk score model using smoking and HRD-related genes in LUSC. The risk score model had high power for predicting 2, 3 and 5-year survival (p<0.01, AUC=0.67, 0.66, 0.66). In addition, the risk scores were independent risk factor for LUSC (HR=2.34, 95%CI=1.70-3.23). The practical nomogram was also built using the risk score, smoking status and other clinical information with good c-index (0.72, 95%CI=0.70-0.74). Finally, we used other TCGA SCC cohorts to confirm the reliability and validity of the risk score model (p<0.01 and AUC>0.6 at 2-,3- and 5-year in CSCC and HNSC cohorts). In conclusion, the present study suggested that smoking cessation should be as a part in smoking-related SCC treatment, and also provided a risk score model to predict prognosis and improve effective of screening platinum/PARP population.